Análise do microbioma vaginal bovino por técnicas dependentes e independentes de cultivo - Mateus Laguardia Nascimento (2015)
Brazil possesses the most important commercial heard in the world and the second largest one, making livestock an important part of the national economy. To date, studies involving cattle microbiota, using both culture dependent and independent methods, focused on the gastrointestinal tract, and little is known about the microbiota of the also important genitourinary tract. This study aimed the microbial characterization of the bovine vaginal tract of heifers and cows, pregnant and non-pregnant, using both culture dependent and independent approaches, as well as the selection of potential probiotics for the treatment of genitourinary infections. Data provided by the culture independent techniques showed great bacterial diversity, but a diminished archaeal and fungal diversity. The main bacterial phyla found were Firmicutes (~40-50%), Bacteroidetes (~15-25%) and Proteobacteria (~5-25%), in addition to ~10-20% non-classified bacteria. A variety of genera dominates this microbiome, although ~45-55% of the samples are represented by only ten OTUs, namely Aeribacillus, Bacteroides, Clostridium, Ruminococcus, Rikenella, Alistipes, Bacillus, Eubacterium, Prevotella and non-classified bacteria. Archaeal samples are dominated by Methanobrevibacter (Euryarchaeota, ~55-70%). Ascomycota is the main fungal phylum (~80-95%) and Mycosphaerella the most abundant genus (~70-85%). These data indicate a great influence of the gastrointestinal microbiota on the colonization of the vaginal tract, event that has already been proposed for other animal species and could be explained by the proximity between these tracts. Hormonal influence was not clear, but a tendency for the reduction of the bacterial population and increase of the archaeal population on pregnant animals was observed. Eukaryotes do not vary significantly among pregnant e non-pregnant animals, but tended to be more abundant on cows than on heifers. A total of 69 bacterial clones were isolated from cultivated samples, most of them (60) belonging to the Escherichia genus. Antagonism, co-aggregation, hydrophobicity, and hydrogen peroxide production tests were performed on 11 isolates, resulting on the identification of three samples with high potential for probiotic use, and four with a median potential. There was clear hormonal and age influence on the abundance of the cultured organisms, with higher isolates abundance in the pregnant group than in the non-pregnant group and in cows than in heifers. The present work describes a great microbial variability on the vaginal community among the tested animals and groups, and a significant difference between the findings using culture dependent and independent methods, pointing the need for further studies on this matter. Vaginal colonization appears to be influenced by the gastrointestinal community.